Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - Review Exercises - Page 152: 17



Work Step by Step

The middlepoint between $(0,0)$ and $(4,-6)$ is the center of the circle: $\frac{(0,0)+(4,-6)}{2}=(2,-3)$, that is: $h=2$, $k=-3$ The distance from the center to an endpoint is the radius: $r=\sqrt {(2-0)^2+(-3-0)^2}=\sqrt {13}$ Equation of a circle: $(x−h)^2+(y−k)^2=r^2$ (standard form) $(x-2)^2+[y-(-3)]^2=(\sqrt {13})^2$ $(x-2)^2+(y+3)^2=13$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.